"Misfits" in fin de siècle France and Italy: anatomies of difference - Ashley, Susan A. (Corpus and Discourse, 2017)
"An exploration of how doctors and social scientists in Fin de siècle France and Italy explained crime, vagrancy, perversion, insanity, neurosis and genius."--